Two Cases of Quadricuspid Aortic Valve: Aortic Regurgitation and Degeneration - Federspiel, Jan Michael; Tschernig, Thomas; Laschke, Matthias Werner; Schäfers, Hans-Joachim (The Thoracic and Cardiovascular Surgeon Reports, 2022)
Background Quadricuspid aortic valve is rare and occasionally associated with aortic regurgitation and ascending aortic dilatation. Recent studies suggest an association of aortic regurgitation with ascending aortic medial degeneration.Case Description Histologic evaluation of ascending aortic tissue of two individuals with regurgitant quadricuspid aortic valve, one dilated, one non-dilated, yielded comparable degeneration in the Media.Conclusion Regurgitation of quadricuspid aortic valve may lead to the degeneration of Tunica media of the ascending aorta.
Keywords: aortic regurgitation; aneurysm; aortic valve; aorta